Pedofilie : een bijdrage tot de oplossing van een maatschappelijk probleem. - Pieterse, Monica (Leiden : Universiteit Leiden, 1978)
Fonds Suzan Daniel (FSD)
Doctoraalscriptie Universiteit Leiden
Nederlands
Proefschrift